Familial hypercholesterolemia: Is there a role for PCSK9 and thrombin generation?. Issue 200 (April 2021) - Silvino, J.P.P.; Carvalho, M.G.; Reis, E.A.; Mota, A.P.L.; Gomes, K.B.; Duarte, R.C.F.; Guimarães, M.C.J.; Sousa, M.C.R.; Azevedo, P.S.; Silva, I.F.O.
Abstract: Introduction: Familial hypercholesterolemia (FH) is an autosomal dominant genetic disease. The prevalence of FH has previously been reported as 1 in 500 in the general population. This study aimed to evaluate the proprotein convertase subtilisin/kexin 9 (PCSK9) levels, lipid profile and thrombin generation in FH patients undergoing treatment or not. Methods: Eighty individuals with FH were selected and distributed in 2 groups: individuals treated with statins alone or conjugate therapy (statin + ezetimibe) ( T  = 53) and those non treated (NT = 27). PCSK9 levels were determined by ELISA, the lipid profile by colorimetric enzyme method and thrombin generation assay (TGA) by CAT method. Results: Individuals treated with conjugate therapy (statin + ezetimibe) showed a significant reduction in the levels of total cholesterol (TC) low density lipoprotein cholesterol (LDLc) and in the potential for thrombin generation (ETP with low and high concentration of tissue factor), compared to the treated individuals with monotherapy (statins). PCSK9 was positively correlated with increased levels of TC, LDLc and triglycerides, while TGA parameters were positively correlated with PCSK9 and lipid profile. Conclusion: PCSK9 levels appear to be associated with components of the lipid and hemostatic profiles, in addition to being influenced by age. In general, our findings suggest that combined therapy for the treatment of FH is associated with a significant improvement in both lipid and hemostatic profiles assessed by TGA, suggesting a reduction in atherogenic and thrombogenic risks and, therefore, more promising compared to the use of statin monotherapy. Highlights: Influence of statin + ezetimibe in lipid and hemostatic (ETPHTF/ETPLTF) profiles. PCSK9 showed a significant increase with aging FH patients. Correlation between PCSK9 levels and TGA parameters in FH patients. TGA may be a guide to therapy in FH for the assessment of thrombogenic risk.